2020
DOI: 10.1183/20734735.0338-2019
|View full text |Cite
|
Sign up to set email alerts
|

Education makes people take their medication: myth or maxim?

Abstract: Cite as: Driever EM, Brand PLP. Education makes people take their medication: myth or maxim? Breathe 2020; 16: 190338. @ERSpublications Education on its own doesn't make people take their treatment as intended. However, when it follows shared decision making, in which patient and doctor together agree on the best course of therapeutic action, education helps patients take their treatment. http://bit.ly/2G2XswD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
3
0
3
Order By: Relevance
“…33 34 35 These findings coincide with other findings showing that shaping the patients' beliefs related to medications and educating them can strongly influence the patients' adherence to treatment. 54 55 Thus, we conclude that technologies should be able to educate patients on how and why they should adhere to treatments to raise their awareness of the importance of complying with their medication and treatment regimens. In addition, the findings showed that personalization, gamification, and motivation were factors that impacted the success of the used technologies.…”
Section: Discussionmentioning
confidence: 94%
“…33 34 35 These findings coincide with other findings showing that shaping the patients' beliefs related to medications and educating them can strongly influence the patients' adherence to treatment. 54 55 Thus, we conclude that technologies should be able to educate patients on how and why they should adhere to treatments to raise their awareness of the importance of complying with their medication and treatment regimens. In addition, the findings showed that personalization, gamification, and motivation were factors that impacted the success of the used technologies.…”
Section: Discussionmentioning
confidence: 94%
“…The better way to ensure someone takes their medicine as prescribed is to achieve a partnership-based education on adherence [ 45 ]. Education is more effective when it is consumer centred and follows a shared decision-making between consumers and healthcare providers to decide the best way to obtain the desired treatment outcome [ 46 ]. Improved information provision and behavioural support focused specifically on medication adherence have shown higher rates of adherence in various clinical conditions such as glaucoma [ 47 ] and rheumatoid arthritis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esto resulta relevante ya que la validación de materiales psicoeducativos ha sido un área poco documentada, sin embargo, se debe considerar su importancia, pues éstos fungen como un medio para que los pacientes accedan a información clave sobre su enfermedad y tratamiento, son elementos complementarios de la atención con el clínico y ofrecen información y recomendaciones estándar a problemas de salud en cualquier momento, sobre todo en contextos en los que resulta difícil contar con la disponibilidad de un profesional especializado del que se pueda obtener información actualizada y basada en evidencia (Driever & Brand, 2020;Kucukarslan, 2016;Miles et al, 2020;Navarro-Rubio et al, 2019); tal y como ocurre en el sistema de salud público de México que tiene una alta demanda, que afecta la atención a pacientes incluido el tiempo que se invierte en explicar la enfermedad y el tratamiento (Secretaria de Salud, 2015).…”
Section: áReasunclassified
“…Desde la lógica de los modelos expuestos, un cambio en las percepciones sobre la enfermedad derivados de intervenciones estructuradas con base en las dimensiones de los modelos MSC/MNP) generaría resultados favorables en las conductas de adherencia y el control del asma, esto debido a que la educación estaría organizada con base en la teoría, en un modelo de cambio conductual y orientada a los factores modificables que explican la falta de adherencia al tratamiento y el control de la enfermedad en estos pacientes (Driever & Brand, 2020;Foot et al, 2019;Horne et al, 2019;Kucukarslan, 2016).…”
unclassified